Dyskursywność klapsa w świetle rodzicielskich narracji - Iga Kisa-Bogorodź (Problemy Wczesnej Edukacji)
In Poland there has been a ban on the use of corporal punishment of children since 2010. However, the results of the research presented in 2018 by The Ombudsman for Children of that time show that more than half of Polish parents use spanking in upbringing. In this paper I would like to find the reason why parents beat children, how they justify including corporal punishment or eliminating it from upbringing and how they perceive the child in mutual relations. A small part of the research presented by me is the result of the research process during which I conducted semi-structured interviews with parents. The material collected as the result of them was subjected to a phenomenographic analysis with the use of elements of the grounded theory and, as a result, three concepts of spanking which will be shown in the text appeared. The results of the research presented indicate that a spank is a discursive phenomenon which is perceived by some people as violence, harm and an unacceptable method in the educational process, and by others it is considered as a valuable, positive and needed element of mutual relations with the child. In the text I do not make an attempt to evaluate parental conceptions of spanking, but only to show the multiplicity of understanding it.